Pleistocene aridification cycles shaped the contemporary genetic architecture of Southern African baboons. - Riashna Sithaldeen; Rebecca Rogers Ackermann; Jacqueline M Bishop (PLoS ONE, 2015)
Plio-Pleistocene environmental change influenced the evolutionary history of many animal lineages in Africa, highlighting key roles for both climate and tectonics in the evolution of Africa's faunal diversity. Here, we explore diversification in the southern African chacma baboon Papio ursinus sensu lato and reveal a dominant role for increasingly arid landscapes during past glacial cycles in shaping contemporary genetic structure. Recent work on baboons (Papio spp.) supports complex lineage structuring with a dominant pulse of diversification occurring 1-2Ma, and yet the link to palaeoenvironmental change remains largely untested. Phylogeographic reconstruction based on mitochondrial DNA sequence data supports a scenario where chacma baboon populations were likely restricted to refugia during periods of regional cooling and drying through the Late Pleistocene. The two lineages of chacma baboon, ursinus and griseipes, are strongly geographically structured, and demographic reconstruction together with spatial analysis of genetic variation point to possible climate-driven isolating events where baboons may have retreated to more optimum conditions during cooler, drier periods. Our analysis highlights a period of continuous population growth beginning in the Middle to Late Pleistocene in both the ursinus and the PG2 griseipes lineages. All three clades identified in the study then enter a state of declining population size (Nef) through to the Holocene; this is particularly marked in the last 20,000 years, most likely coincident with the Last Glacial Maximum. The pattern recovered here conforms to expectations based on the dynamic regional climate trends in southern Africa through the Pleistocene and provides further support for complex patterns of diversification in the region's biodiversity.